Humor and Linguistic Creativity through Code-Switching: A Pragmatic-Sociolinguistic Analysis of Indonesian–English Youth Podcasts - Sari, Lusi Komala; Ardana, Sindi; Onwuagboke, Bede Blaise Chukwunyere (Actual Insight, 2025)
This study examines the use of humor, code-switching, and linguistic creativity in Indonesian–English bilingual podcasts oriented toward adolescents, with a particular focus on their pragmatic functions in digital communication, social interaction, and audience engagement. Grounded in sociolinguistic and pragmatic perspectives, particularly Gumperz’s (1982) theory of interactional code-switching and the General Theory of Verbal Humor proposed by Attardo and Raskin (1991), the study explores how bilingual practices are mobilized in podcast discourse. Employing a qualitative discourse-pragmatic approach, selected podcast excerpts are analyzed to identify patterns of humor including situational humor, self-deprecating humor, wordplay, and absurdity as well as strategic code-switching and linguistic creativity devices such as metaphors, neologisms, and creative categorization. The findings indicate that humor and code-switching function synergistically to convey social meanings, articulate speaker stance, and enhance audience appeal, while linguistic creativity expands the expressive potential of the discourse. These findings contribute to the growing scholarship on humor and code-switching in the Indonesian digital media context and offer practical implications for podcast-based language pedagogy aimed at fostering bilingual competence and pragmatic awareness.